1998
DOI: 10.1103/physrevb.57.7292
|View full text |Cite
|
Sign up to set email alerts
|

Formation and healing of defects at theSi(111)7×7surface under low-energy ion bombardment

Abstract: We studied the formation and healing of adatom defects on a Si(111)7ϫ7 surface bombarded by 0.5-keV Ar ions. Scanning tunneling microscopy showed that adatoms were missing from the Si(111)7ϫ7 surface. Increasing the temperature during the bombardment increased the percentage of missing adatom sites. However, the percentage saturated at 400 K, then decreased with temperature. This temperature dependence was due to competition between the formation and healing of adatom defects; defect formation dominated at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…On a Si(111)7ϫ7 surface, bombardment with rare-gas ions has been reported to sputter surface adatoms in the low-energy range. [10][11][12][13] Our experiments found similar effects during irradiation with 200 eV Ar ϩ ion on Si(111)7ϫ7 surface at an incidence angle of 20°. Since the dimer, adatom, and stacking fault layers have unique signatures in the diffraction pattern, it is possible to measure the initial rate of erosion directly from the estimation of the missing atoms in each layer.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On a Si(111)7ϫ7 surface, bombardment with rare-gas ions has been reported to sputter surface adatoms in the low-energy range. [10][11][12][13] Our experiments found similar effects during irradiation with 200 eV Ar ϩ ion on Si(111)7ϫ7 surface at an incidence angle of 20°. Since the dimer, adatom, and stacking fault layers have unique signatures in the diffraction pattern, it is possible to measure the initial rate of erosion directly from the estimation of the missing atoms in each layer.…”
Section: Discussionsupporting
confidence: 67%
“…Previous work has involved mainly STM measurements made on a Si(111)7ϫ7 surface to study the surface defects formed by rare-gas ions in the energy ranges between 200 eV to 3 keV. [10][11][12][13][14] They observed that low energy (Ͻ500 eV) Ar or Xe ion bombardment on Si(111)7ϫ7 surface leads to clearly identified surface defects. These surface defects are populated by adatom vacancy regions, where adatoms have been removed by ion impact.…”
Section: Introductionmentioning
confidence: 99%
“…12 Our real-time high-temperature STM observations of the ion-irradiated surface enable us to monitor the sequential size changes of defects after ion irradiation. In their experiment, the surface defects shrink monotonically due to the atom supply from two-dimensional ͑2D͒ atom gas.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 The base pressure of the treatment and main chambers was less than 2 ϫ10 Ϫ8 Pa. The samples, with dimensions of 2.5 mm ϫ7.0 mmϫ0.2 mm, were cut from a low doped n-type Si͑111͒ wafer (ϭ1.5 ⍀ cm).…”
Section: Methodsmentioning
confidence: 99%